FOLLICULAR VARIANT OF PTCA INITIALLY PRESENTING AS WIDESPREAD METASTASES - Bisquera, Nichole Andrea; Mirasol, Roberto (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Papillary thyroid carcinoma accounts for most cases of thyroid cancer with most cases having good prognosis and low incidence of metastases. The follicular variant (FV) is the most common. First described in the 1960s, the understanding of FV-PTC began to evolve with molecular profiling demonstrating a similarity with FTC, and clinical behavior profiling showing that a subtype may behave like PTC with a propensity for lymph node metastases. We are presented with an unusual case of an infiltrative FVPTC presenting with widespread multiple metastases on diagnosis. A 64-year-old female presented with a 1-year history of a slowly enlarging mass on the left mandible, associated with an enlarging anterior neck mass. On examination, there was a 7 x 8 x 3 cm hard, fixed, left mandibular mass and a palpable right thyroid nodule measuring 2.5 x 2 cm. There was no difficulty in swallowing or breathing, but she had some difficulty in eating due to trismus. There were no associated symptoms of hypo- nor hyperthyroidism. Investigations revealed a euthyroid status. CT scan showed a solid lobulated heterogeneously enhancing mass measuring 4.2 x 5.1 x 5.2 cm on the body and angle of the left mandible. Ultrasound showed multiple thyroid nodules, the largest - a mixed cystic and solid mass measuring 2.9 x 2.7 x 2.17 cm on the right thyroid lobe, for which FNA was performed. Histopathology showed benign follicular nodules. An incision biopsy of the mandibular mass showed the presence of thyroid tissue. Further imaging showed metastases to the left frontal and parietal bone, T7 vertebra, and bilateral lungs. With a preoperative diagnosis of a primary thyroid malignancy, the case was discussed in a multi-disciplinary tumor board meeting. The patient then underwent total thyroidectomy with segmental mandibulectomy. Histopathology postop showed a metastatic multifocal infiltrative follicular variant of PTC. RAI was administered post-surgery and suppressive thyroxine therapy was started. Steroids were given during RAI, with no untoward events posttreatment. Post-ablative whole-body scanning revealed increased tracer uptake in multiple areas: left frontal and parietal bone, bilateral thyroidal beds, left supraclavicular lymph node, the sternomanubrial junction, bilateral lung lobes, right humeral head, and T7 vertebra. Further doses of RAI were planned and she is currently maintained on suppressive thyroxine therapy. Diagnosis of FV-PTC may be a greater challenge than conventional forms because of possible false-negative results on cytology. The infiltrative subtype has greater metastatic potential and higher recurrence rates. Multidisciplinary team management and careful preparation prior to treatment with RAI are indicated in these cases.